Effect of Incorporation of Boron Nitride Nanoparticles on Impact Strength and Surface Roughness of Heat Cure Poly Methyl Methacrylate Resin: An In Vitro Study - Hussein Ali M Hussein; Hikmat J Al-Judy (Wolters Kluwer Medknow Publications, 2023)
Background: The objective of this research was to explore how the addition of boron nitride (BN) nanoparticles in the concentrations of 1% and 1.5% w/w affect the impact strength and surface roughness of heat-cured poly methyl methacrylate resin (PMMA). Methods: Sixty specimens were made from heat-cured acrylic resin and then divided into control, 1%, and 1.5% w/w BN groups. The impact strength and surface roughness were investigated. One-way ANOVA and Tukey's post hoc test were used for data analysis. Results: Statistically significant difference is found among the three study groups regarding impact strength (P = 0.011) and surface roughness test (P <  0.001). The post hoc test showed significant differences for all multiple comparisons for the surface roughness test (P < 0.001). Yet, multiple comparisons for the impact strength test revealed only a significant difference between the 1.5% BN and control groups (P = 0.005). Conclusion: The addition of boron BN into PMMA improves impact strength with 1.5% concentration; while adversely increase the surface roughness.